Development of Digital Comic Genetic Engineering Based on Android with Integrated Islamic Values - Syaferi, Akhmad; Widowati, Hening; Sutanto, Agus (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Technological advances encourage learning media innovations, one of which is digital comics. This study aims to develop digital comics with the theme of genetic engineering integrated with Islamic values using the ADDIE model (analyze, design, development, implementation, and evaluation). The results of the needs analysis showed that 90% of students had difficulty understanding the concept of genetic engineering, while 87% were interested in using digital comics as learning media. The developed digital comics were validated by three experts, namely material, media, and Islamic values experts, with the percentage of feasibility of 85%, 98%, and 92%, respectively, all of which were included in the category of “very feasible.” The results of the trial conducted with one teacher obtained an average percentage of 98%, while the trial with 30 students obtained an average percentage of 88%, both in the “very good” category.  These findings indicate that digital comics are feasible to use as biology learning media in high school with interactive audio-visual advantages. Further research is recommended to focus on measuring the achievement of learning objective criteria to determine the impact of using this digital comic on improving overall student learning outcomes.